Management of Ventral Abdominal Hysterocele in a Pregnant Queen - Shreemathi, Ravi; Selvaraju, Mani; Ruthrakumar, Ravichandran; Jawahar Vinayaga, Senthil Kumar; pikrishnan, Duraisamy Go; Palanisamy, Mahakrishnan (The Indian Journal of Animal Reproduction, 2026)
A one-year-old pregnant Domestic Short-Haired queen was presented with a recent history of swelling in the right ven tral abdominal region following suspected trauma. Clinical palpation revealed a non-reducible soft mass with detectable fetal structures. Haematological findings indicated leucocytosis with mild anaemia. Radiography confirmed the pres ence of three foetal skeletons within the herniated area, and ultrasonography revealed non-viable foetuses surrounded by excessive anechoic fluid. Based on clinical and imaging findings, the condition was diagnosed as ventral abdominal hysterocele. Surgical intervention consisting of ovariohysterectomy followed by herniorrhaphy was performed under general anaesthesia. Postoperative recovery was uneventful, and complete healing was observed. Early diagnosis and prompt surgical management ensured a favourable outcome.
Keywords: herniorrhaphy; Hysterocele; Inguinal hernia; Ovariohysterectomy